POLLEN AND FUNGAL SPORE COMPOSITION VARIATIONS OF HONEYS ACCORDING TO DIFFERENT FEEDING METHODS - Yil, Gulsah; Karlidag, Semiramis; Akyol, Abuzer; Koseman, Abdurrahman; Uyumlu, Ayse Burcin; Yilmaztekin, Murat; Seker, Ibrahim (Pakistan Botanical Soc, 2023)
Honey samples were collected from two districts of Malatya (Eastern Turkey) Battalgazi and Dogansehir for melissopalynological analysis after the honey season in 2018. The survey was conducted to 3 different feeding groups, Glucose, Sucrose, Bee Feed and a Control group in each study area. The samples were prepared according to Louveaux et al., (1978) procedure. Melissopalynological examinations were done to determine both pollen grains and fungal spores for each feeding group and districts. According to the microscopic analyses the dominant pollen types were determined as Astragalus, Cistus, Poaceae, Verbascum, Echium, Berberis, Artemisia, Plantago, Vicia, Onobrychis, Cichorioideae, Astragalus pollen grains were most frequent in glucose and control groups, Cistus pollen grains were widely represented in sucrose and bee feed groups in both study area. Dominant fungal spore types were determined as Aspergillus / Penicillium, Urediniospores, Cladosporium and Myrotechium. Aspergillus / Penicillium spores were dominated almost all samples by varying degrees. Analysis of pollen grains and fungal spores is useful instrument for determining the botanical, geographical and ecological sources of honey. This paper could be guide to beekeepers for selecting convenient apiary domains and appropriate feeding methods for qualitative honeys and the study is also help agriculturists for increasing the crop yield, the bees could be diverting to less-preferred plants during forages by sugar manipulation in order to cultivation improving.
Keywords: Honey; Pollen; Fungal spores; Malatya; Turkey